Validity and reliability of the oral health‐related caregiver burden index. (12th July 2017) - Matsuda, Yuhei; Izumi, Maya; Nakamichi, Atsuko; Isobe, Ayaka; Akifusa, Sumio
Abstract : Objective: This study developed the Oral Health‐related Caregiver Burden Index (OHBI), which contains nine questions with five response options each. As a secondary objective, we aimed to clarify the relationship between oral health‐related caregiver burden and general caregiver burden. Background: There are a few reports of the oral health‐related caregiver burden. Methods: Between January 2016 and February 2016, 155 participants enrolled in the study. We conducted the survey to examine the validity and reliability of OHBI. Additionally, the cut‐off score for this scale was calculated, and the relationship between OHBI and general caregiver burden (BIC‐11) was examined by binomial logistic regression. Results: Survey 1 was completed by 102 caregivers, of whom 58 (56.9%) were female. Survey 2 was completed by 40 caregivers, of whom 22 (55.0%) were female. Factor analysis revealed four factors in OHBI. Cronbach's α was .691‐.866. OHBI scores were significantly associated with scores for each factor of the BIC‐11. OHBI had a cut‐off score of 10 (AUC=.881, sensitivity=.828, specificity=.744). A good‐poor analysis revealed significant differences for discriminant validity. ICC, an indicator of reliability, was .449‐.842. There was a significant relationship between caregiver burden and oral health‐related caregiver burden according to binomial logistic regression analysis ( P <.05). Conclusion: We developed the OHBI as a multidimensional care burden scale, which comprises nine items covering five domains. Further, we verified the relationship between general caregiver burden and oral health‐related caregiver burden.